Smith–Petersen Versus Watson–Jones Approach Does Not Affect Quality of Open Reduction of Femoral Neck Fracture. Issue 10 (October 2021) - Patterson, Joseph T.; Ishii, Keisuke; Tornetta, Paul; Leighton, Ross K.; Friess, Darin M.; Jones, Clifford B.; Levine, Ari; Maclean, Jeffrey J.; Miclau, Theodore; Mullis, Brian H.; Obremskey, William T.; Ostrum, Robert F.; et al.
Abstract : Objective: To compare immediate quality of open reduction of femoral neck fractures by alternative surgical approaches. Design: Retrospective cohort study. Setting: Twelve Level 1 North American trauma centers. Patients: Eighty adults 18–65 years of age with isolated, displaced, OTA/AO type 31-B2 or -B3 femoral neck fractures treated with internal fixation. Intervention: Thirty-two modified Smith–Petersen anterior approaches versus 48 Watson–Jones anterolateral approaches for open reduction performed by fellowship-trained orthopaedic trauma surgeons. Main outcome: Reduction quality as assessed by 3 senior orthopaedic traumatologists as "acceptable" or "unacceptable" on AP and lateral postoperative radiographs. Results: No difference was observed in the rate of acceptable reduction by modified Smith–Petersen (81%) versus Watson–Jones (81%) approach (risk difference null, 95% confidence interval −17.4% to 17.4%, P = 1.00) with 90.4% panel agreement (Fleiss' weighted κ = 0.63, P < 0.01). Stratified analyses did not identify a significant difference in the rate of acceptable reduction between approaches when stratified by Pauwels angle, basicervical or transcervical fracture location, or posterior comminution. The Smith–Petersen approach afforded a better reduction when preoperative skeletal traction was not applied (RR = 1.67 [95% CI 1.10–2.52] vs. RR = 0.87 [95% CI 0.70–1.08], P = 0.006). Conclusions: No difference was observed in the quality of open reduction of displaced femoral neck fractures in young adults when a Watson–Jones anterolateral approach versus a modified Smith–Petersen anterior approach was performed by orthopaedic trauma surgeons. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.